Impact of governance on the social responsibility of sports institutions in Kirkuk Governorate - Saber, Mohammed Ahmed; Mohamed Ibrahim , AlShaima (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
This study aimed to identify the level of governance and its effectiveness within sports institutions, and the level of social responsibility of workers within sports institutions. It was used a descriptive approach (survey). Sample participants were recruited using comprehensive inventory method from sports clubs, sports federations and the Olympic Committee. A total of 176 individuals were recruited as the sample for the study. Out of 176 individuals, the researchers distributed 161 questionnaires to the study sample, and then took a sample of 15 people to validate the questionnaire. Based on the findings of the study, the researchers concluded that there was a lack of application of principles of governance within the sports institutions in Kirkuk Governorate (Iraq), and that there was weakness of social responsibility towards society and the environment, and towards workers and employees within the sports institutions in Kirkuk Governorate.